2013
DOI: 10.5194/nhess-13-1595-2013
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of static flood modeling techniques: application to contrasting marshes flooded during Xynthia (western France)

Abstract: This study aims to assess the performance of raster-based flood modeling methods on a wide diversity of coastal marshes. These methods are applied to the flooding associated with the storm Xynthia, which severely hit the western coast of France in February 2010. Static and semi-dynamic methods are assessed using a combination of LiDAR data, post-storm delineation of flooded areas and sea levels originating from both tide gauge measurements and storm surge modeling. Static methods are applied to 27 marshes show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
86
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(94 citation statements)
references
References 51 publications
5
86
0
3
Order By: Relevance
“…Dynamic inundation simulations have been shown to be more reliable (Ramirez et al, 2016). However, Vousdoukas et al (2016) have shown that VI can be a good surrogate when computational efficiency is the priority, as also demonstrated by Breilh et al (2013). In flatter terrains, VI tends to be outperformed by hydraulic models, or other empirical approaches, such as the flood index method (Dottori et al, 2016a).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dynamic inundation simulations have been shown to be more reliable (Ramirez et al, 2016). However, Vousdoukas et al (2016) have shown that VI can be a good surrogate when computational efficiency is the priority, as also demonstrated by Breilh et al (2013). In flatter terrains, VI tends to be outperformed by hydraulic models, or other empirical approaches, such as the flood index method (Dottori et al, 2016a).…”
Section: Discussionmentioning
confidence: 99%
“…This approach is presented as "SO" in Breilh et al (2013) and assumes a design hydrograph driven by meteorological factors that is added to the high-tide water level to calculate the timedependent total water level. The design storm surge hydrograph requires information about the extreme event duration D CE .…”
Section: Coastal Inundationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, given the high complexity of coastal flooding processes, several recent studies showed that the static approach results in substantial overestimation of the flood extent compared to dedicated hydraulic models, especially in flatter terrains (Breilh et al, 2013;Gallien, 2016;Ramirez et al, 2016;Seenath et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Sin embargo, a pesar de la amplia extensión que alcanzan estas formas en muchas áreas costeras, desde un punto de vista geomorfológico prácticamente no han recibido atención. Aparte de algunas aproximaciones multidisciplinares o locales (Pérez Hurtado, 2004), las investigaciones se han centrado hasta la fecha básicamente en los procesos actuales de inundación y sedimentación en marismas naturales (Pethick, 1992;Torres et al, 2006;Breilh et al, 2013), o el impacto antropogénico y la regeneración ambiental de marismas antropizadas (Irabien et al, 2008;García-Artola et al, 2011), desatendiendo cuestiones como la influencia de la dinámica natural en la elección de lugares para la instalación de salinas, las modificaciones que estas formas ejercen sobre los procesos naturales, o las consecuencias morfológicas y dinámicas de su abandono y degradación.…”
Section: Introductionunclassified